The Implementation of Learning Journal to Improve University Students’ Motivation in Basic and Process of Learning Biology Subject - Ali Sadikin (Universitas Negeri Padang Address: Biology Education Study Program Faculty Mathematics and Natural Science (FMIPA) Jl. Prof. Dr. Hamka Air Tawar Barat, Padang-West Sumatera-Indonesia Telp. +62751-7057420 - Fax.+62751-7058772 - Ph. +6281363229286, 2018)
This research conducted to improve university students’ motivation in basic and process of learning biology subject in Biology Education Study Program Universitas Jambi through implementation of learning journal. This research have done by two cycle, which each cycle done with four steps, include planning, action, observation, and reflection. The result show that percentation score before action is 67% in enough criteria, in first cycle up to be 76,25% with good criteria, and in the second cycle increase to 76,25% also in good criteria. In conclusion, implementation of learning journal can increase learning motivation.